Laccase Directed Lignification Is One of the Major Processes Associated With the Defense Response Against Pythium ultimum Infection in Apple Roots - Zhu, Yanmin; Li, Guanliang; Singh, Jugpreet; Khan, Awais; Fazio, Gennaro; Saltzgiver, Melody; Xia, Rui (Frontiers in Plant Science, 2021)
Apple replant disease (ARD) causes stunted growth or death of newly planted trees at replant sites. Development and deployment of resistant or tolerant rootstocks offers a cost-effective, ecologically friendly, and durable approach for ARD management. Maximized exploitation of natural resistance demands the integrated effort to identify the key components and regulation mechanisms underlying resistance traits in apple. In this study, candidate genes were identified by miRNA profiling and target gene identification using six apple rootstock genotypes with contrasting resistance phenotypes. The comprehensive RNAseq dataset offered an expansive view of post-transcriptional regulation of apple root defense activation in response to infection from P. ultimum, a necrotrophic oomycete soilborne pathogen. Several pairs of miRNA families and their corresponding targets were identified, including miR397-laccase, miR398-superoxide dismutase, miR10986-polyphenol oxidase, miR482-resistance genes and miR160-auxin response factor. Among them, the genotype-specific expression patterns of the miR397 family members indicated its pivotal role in shaping up the resistance traits to P. ultimum infection. Combined with other identified copper proteins, the importance of cellular fortification, such as lignification of root tissues by the action of laccase, may have critically contributed to genotype-specific resistance responses. Our findings suggest that a quick and enhanced lignification of apple root may significantly impede pathogen penetration and minimizes the disruption of effective defense activation in root of resistant genotypes. The identified target genes and related pathways consist of a valuable resource for subsequent functional analysis of their roles during interaction between apple root resistance and P. ultimum.